First successful production of adult corals derived from cryopreserved larvae - Narida, Arah; Tsai, Sujune; Hsieh, Wen-Chung; Wen, Zhi-Hong; Wang, Li-Hsueh; Huang, Cheng-Liang; Lin, Chiahsin (Frontiers in Marine Science, 2023)
Coral reefs worldwide are declining due to increasing concentrations of greenhouse gases, which, combined with local anthropogenic pressure, are exacerbating unprecedented mass coral bleaching. For corals to survive, restoring coral reefs through cryopreservation is crucial. The aim of this study was to vitrify and laser-warm Stylophora pistillata planulae to allow for feasible settlement, post-settlement survival, and the production of adult corals. The no-observed-effect concentrations were used to determine the best cryoprotective agents for S. pistillata. The larvae were then subjected to cooling and nanolaser warming (300 V, 10 ms pulse width, 2 mm beam diameter) by using two vitrification solutions (VSs; VS1: 2 M dimethyl sulfoxide and 1 M ethylene glycol and VS2: 2M EG and 1M DMSO and gold nanoparticles. The results revealed that VS1-treated larvae had a higher vitrification rate (65%), swimming rate (23.1%), settlement rate (11.54%), and post settlement survival rate (11.54%) than those treated with VS2. Seasonal variations also affected the cryopreservation of the planulae; VS1 was more favorable for the planulae in spring than in fall. Although laser-warmed larvae developed slower morphologically than their controlled counterparts, the production of adult S. pistillata corals from cryopreserved larvae was achieved. The proposed technique can improve the cryopreservation of corals and advance efforts to protect endangered coral species.